2015
DOI: 10.1371/journal.pone.0136593
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Hemocytes Induces a Shift in Effector Mechanisms in the Drosophila Immune System and Leads to a Pro-Inflammatory State

Abstract: Apart from their role in cellular immunity via phagocytosis and encapsulation, Drosophila hemocytes release soluble factors such as antimicrobial peptides, and cytokines to induce humoral responses. In addition, they participate in coagulation and wounding, and in development. To assess their role during infection with entomopathogenic nematodes, we depleted plasmatocytes and crystal cells, the two classes of hemocytes present in naïve larvae by expressing proapoptotic proteins in order to produce hemocyte-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 41 publications
(74 reference statements)
5
48
2
Order By: Relevance
“…melanogaster, a strain resistant to the endoparasitoid wasp, Leptoplina boulardi, produces a significant increase in NO concentrations from differentiated lamellocytes [47], and the elevated NO level mediates hemocyte encapsulation of the parasitoid eggs [16]. NO also acts in humoral immunity by inducing genes encoding AMPs in insects.…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster, a strain resistant to the endoparasitoid wasp, Leptoplina boulardi, produces a significant increase in NO concentrations from differentiated lamellocytes [47], and the elevated NO level mediates hemocyte encapsulation of the parasitoid eggs [16]. NO also acts in humoral immunity by inducing genes encoding AMPs in insects.…”
Section: Discussionmentioning
confidence: 99%
“…As melanization is a rapid process, these cells would be excluded from the pathogen infection experiments. Additionally, the anti-coagulant phenylthiourea can be added to DHIM to inhibit the phenoloxidase-activating system and melanization during wounding 9 . Nevertheless, as melanization and apoptosis are innate immune responses of Drosophila , their levels can be quantified following hemocyte extraction and stimulation using the methods described here.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocytes have been used for morphological observations 5,6,7 , morphometric analysis 2,8 , phagocytosis analysis 2,3 , qRT-PCR 2,9 , immunoprecipitation 10,11 , immunofluorescent analysis 10,12 , immunostaining 13 , immunoblotting 3,10,11 and immunohistochemistry 9,14 . Although Drosophila S2 cells are also available for various in vitro experiments, immortalization and potential pre-existing viral infection change their behavior 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, for the most part macrophages may not be essential during pupariation and adulthood. Animals with genetically ablated hemocytes are viable [174, 175], although developmental defects have been found at low penetrance [174, 176]. …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cellular immunity may have additional functions over the course of infection, not just in the short-term. However, alternative scenarios are possible, as it was recently shown that hemocyte ablation leads to a shift in inflammation status, with an upregulation of Toll signaling and downregulation of the Imd pathway [176]. Interestingly, adult macrophage responses may also be linked to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%